Literasi Digital Pada Anak Usia Dini Untuk Menghadapi Era Digital Di SDN Kemuning Lor 01 - Tanaya Yonas, Cory; Marsidi; Aulia Fajar, Mohammad; Aldiyanto, Muhammad; Irvan Kholid, Muhammad; Widy Priyanti, Putri; Soleha, Siti; Restiana Fitri, Syarifah; Silvia, Zulfa (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This study aims to enhance digital literacy among students at SDN Kemuning Lor 01 through a socialization and education program initiated by KKN Kolaborative 164 students. The research method used is an interactive approach with initial (pretest) and final (posttest) assessments to measure students' knowledge of digital literacy. The results indicate that most students have limited knowledge of safe and responsible smartphone usage. The education provided successfully increased students' understanding of digital literacy, as evidenced by the improvement in posttest results compared to pretest. Early digital literacy education is crucial in equipping children with the necessary skills to navigate the increasingly complex digital era. Therefore, digital literacy should be prioritized in primary education to prepare future generations for the challenges of modern technology.